2020
DOI: 10.1101/2020.10.22.20217661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmission of COVID-19 in the state of Georgia, United States: Spatiotemporal variation and impact of social distancing

Abstract: Background Beginning in early February 2020, COVID-19 spread across the state of Georgia leading to 258,354 cumulative cases as of August 25, 2020. The time scale of spreading (i.e., serial interval) and magnitude of spreading (i.e., Rt or reproduction number) for COVID-19, were observed to be heterogenous by demographic characteristics, region and time period. In this study, we examined the COVID-19 transmission in the state of Georgia, United States. Methods During February 1-July 13, 2020, we identified 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Several studies have examined the R t estimates with respect to policy and interventions and used R t estimates as predictive models and quantitative measures of epidemic growth or decline. [31] , [32] , [33] Here, the R t trajectories of Arkansas and Kentucky differed among rural and urban areas, increasing or decreasing, depending on the implementation of preventative and relaxation measures. The R t will be useful as the pandemic progresses to inform policymakers and public health professions of the direction of potential outbreaks, assisting in preventing health care surges and implementing more preventative measures and policies.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have examined the R t estimates with respect to policy and interventions and used R t estimates as predictive models and quantitative measures of epidemic growth or decline. [31] , [32] , [33] Here, the R t trajectories of Arkansas and Kentucky differed among rural and urban areas, increasing or decreasing, depending on the implementation of preventative and relaxation measures. The R t will be useful as the pandemic progresses to inform policymakers and public health professions of the direction of potential outbreaks, assisting in preventing health care surges and implementing more preventative measures and policies.…”
Section: Discussionmentioning
confidence: 93%
“…as compared to transmission in public spaces. 14 The same study found that the majority of transmission came from people aged 40-70 years at the very beginning of the pandemic but shifted to those aged 25-50 years in June-July, 2020. 14 Males had a higher mortality rate than females in Georgia from COVID-19, with 23% mortality for males versus 13.8% for females.…”
Section: Sociodemographic Differences Among Covid-19 Cases In Georgiamentioning
confidence: 93%
“…14 The same study found that the majority of transmission came from people aged 40-70 years at the very beginning of the pandemic but shifted to those aged 25-50 years in June-July, 2020. 14 Males had a higher mortality rate than females in Georgia from COVID-19, with 23% mortality for males versus 13.8% for females. 11 Males were also hospitalized for COVID-19 more than females, even after controlling for various other factors such as age and chronic conditions.…”
Section: Sociodemographic Differences Among Covid-19 Cases In Georgiamentioning
confidence: 93%
See 1 more Smart Citation
“…A few studies have accessed the effectiveness of mitigation measures, especially regarding face mask mandate and school reopening. [21][22][23] Among the five states, North Dakota, Montana and Wyoming implemented the mask mandate and followed with the Rt reduction, which echoed with the 313 current existing body of research on the efficacy of face masking in preventing the transmission 314 of SARS-CoV-2. [24][25][26] However, South Dakota and Idaho also experienced the Rt reduction 315 without adopting the mask mandate, perhaps due to voluntary adoption of facemasks, which will 316 require further investigation.…”
mentioning
confidence: 99%